Analisis Sensitivitas Pengaruh Calcium Chloride terhadap Perkembangan Strength Semen Pemboran Kelas “G” - Bayu Ogi Saputra; Aprilno Alfa Kurmasela; Abdul Gafar Karim (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The cementing operation aims to bond the casing to the well wall, protect the casing from mechanical disturbances and corrosion, and isolate the formation layer. A decrease in cement strength can cause the formation of gaps behind the casing, thus triggering fluid migration between zones. This study aims to analyze the effect of adding Calcium Chloride (CaCl₂) additives on the strength of drilling cement. Testing used API Class G cement with variations of CaCl₂ of 2% and 4% and curing times of 6, 16, and 24 hours. The parameters tested included Compressive Strength (CS) and Shear Bond Strength (SBS). The results showed that the addition of 4% CaCl₂ produced the highest CS value of 2,711.383 psi at 24 hours of curing, while the highest SBS value was obtained with the addition of 2% CaCl₂ at 303.212 psi at 24 hours of curing. Thus, CaCl₂ effectively increases CS, but higher concentrations tend to decrease SBS.